Paul among the Fluent in Corinth: Introducing Paul and the “Associated Behaviours” of Stuttering into the Study of Dysfluency in Antiquity - Last, Richard (Novum Testamentum, 2022)
This article foregrounds the importance of Paul’s letters for studying the experiences and perceptions of persons who stutter in antiquity. It analyzes Paul’s speech alongside the biographies of two other historical figures from antiquity who suffered from speech dysfluency: the great Athenian orator, Demosthenes, and the emperor Claudius. Accounts of Demosthenes’, Claudius’, and Paul’s speech inconsistencies, silences, incomprehensible utterances, oratory weaknesses—and their critics’ accusations that they suffered from madness—are interpreted in light of research on adults who stutter in the contemporary context, as well as studies on listener experiences and stereotypes. In introducing Paul into the study of ancient dysfluency, the article revisits Paul’s conflict with rival teachers in Corinth as it is in responding to these critics’ accusations that Paul is most revealing of his own dysfluency.